Enzymatic saccharification and lactic acid production from banana pseudo-stem through optimized pretreatment at lowest catalyst concentration - Adnan, Ahmad; Idrees, Muhammad; Malik, Farnaz; Qureshi, Fahim Ashraf (Technische Universität Dortmund, 2013)
This work estimates the potential of banana pseudo-stem with high cellulosic content 42.2- 63 %, for the production of fermentable sugars for lactic acid production through statistically optimized pretreatment method. To evaluate the catalyzed pretreatment efficiency of banana pseudo stem based on the enzymatic digestibility, Response Surface Methodology (RSM) was employed for the optimization of pretreatment temperature and time using lowest concentrations of H2SO4, NaOH, NaOH catalyzed Na2S and Na2SO3 that seemed to be significant variables with P<0.05. High F and R2 values and low p-value for hydrolysis yield indicated the model predictability. The optimized condition for NaOH was determined to be conc. 1 %, temperature 130 oC for 2.6 hr; Na2S; conc. 1 %, temperature 130 oC for 2.29 hr; Na2SO3; conc. 1 %, temperature 130 oC for 2.41 hr and H2SO4; conc. 1 %, temperature 129.45 oC for 2.18 hr, produced 84.91 %, 85.23 %, 81.2 % and 76.02 % hydrolysis yield, respectively. Sulphuric acid provided 33+1 gL-1 reducing sugars in pretreatment step along with 38+0.5 gL-1 during enzymatic hydrolysis. Separate hydrolysis and fermentation of resulting sugars showed that the conversion of glucans into lactic acid reached 92 % of the theoretical yield of glucose.
EXCLI Journal ; Vol. 12, 2013
Keywords: digestibility; fermentable sugars; glucans; lactic acid; optimized pretreatment; 610